(untitled) (Літератури світу: поетика, ментальність і духовність, 2017)
This article represents citizen images in terms of occupation fascist regime through the prism of psychopoetics. The author points at the fact that H. Huseynov describes not only the life of the mindset steppe city inhabitants under conditions of the occupation regime, but also he draws attention to the perception of changes in the way of living conditions among people of different ages and social groups. The city has a principle of social hierarchy. So, in terms of the occupation regime considerable changes in system regulations are performed. The way of thinking among the inhabitants evolves significant modifications. The city being under conditions of occupation regime keeps on living its own life, but all the previous life and behavior regulations fade into the background.